Impact of increasing atmospheric concentration of carbon dioxide on coffee leaf rust and coffee plant growth - Oliveira Tozzi, Fernanda Ribeiro [UNESP]; Ghini, Raquel (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to evaluate the effect of increasing the atmospheric concentration of carbon dioxide on plant growth and leaf rust severity (caused by Hemileia vastatrix) on coffee (Coffea arabica). The 'Obata IAC 1669-20' and 'Catuai Vermelho IAC 144' cultivars, moderately resistant and susceptible to the disease, respectively, were used. The treatments consisted of 400 and 508 mu mol mol(-1) atmospheric CO2, in two types of open-top chambers (OTC). Plants of the two cultivars, grown in OTCs with addition of CO2, showed increased leaf area, and increased growth rate of height and stem diameter, in comparison with plants in OTCs with ambient CO2 concentration; however, the cultivars did not differ for leaf-wax content. On 'Catuai Vermelho IAC 144', rust severity reduced at increased CO2 concentration, for number of lesions, lesioned leaf area, number of sporulated lesions, sporulated leaf area, percentage of lesioned area, and area under disease progress curve; however, on 'Obata IAC 1669-20', the disease severity did not vary. The incidence of lesioned leaves per plant, latent period, urediniospore germinations, and appressorium formation are not changed by the 508 mu mol mol(-1) CO2 dose in both cultivars.
Keywords: Coffea arabica; Hemileia vastatrix; global warming; CO2; climate change